Ageing with apps: A Foucauldian study exploring older people’s use of apps in managing their physical health - Bavngaard, Martin (MedieKultur: Journal of media and communication research, 2023)
This article explores the incorporation of mobile applications in older people’s physical health management through the lens of Foucault’s concepts on self-governance. Based on ten interviews with older Danes, the article posits that physical health management practices constitute practices of self-governance, involving participants’ attunement to both physical activity and bodily phenomena, which are both facilitated and optimized through app-based self-tracking. The findings align the rationales driving participants’ efforts with the trajectory of the governmental concept of active ageing. Using apps thus becomes intertwined with participants’ efforts towards ageing successfully, consequently taking on a dual function: Apps strengthen the adherence to norms of conduct for achieving an optimal ageing process by allowing for ubiquitous self-monitoring and self-assessment. Simultaneously, I argue that apps may also act as a gatekeeper, as lacking the technical competencies to efficiently use apps hinders effective health management and thus clashes with efforts conforming to active ageing.